Auditory wavelet packet filters for multistyle classification of speech under stress - Nurul Aida Amira, Johari (IEEE Conference Publications, 2014)
Proceeding of The International Conference on Control System, Computing and Engineering (ICCSCE 2011) at Penang, Malaysia on 25 November 2011 through 27 November 2011